What has really happened to poverty in the Philippines? New measures, evidence, and policy implications - Arsenio M. Balisacan (University of the Philippines, School of Economics (UPSE), 2011)
That poverty is a multidimensional phenomenon is no longer debatable. What remains a contentious issue is whether the various dimensions of individual deprivation should be aggregated
Keywords: I32; O15; O53; 330; and how these are to be aggregated; Armut; Soziale Lage; Entwicklungsindikator; Philippinen